1997
DOI: 10.1177/096120339700600612
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B and C viruses serology in patients with SLE

Abstract: Sera of 95 patients with SLE were tested for the presence of hepatitis B surface antigen (HBsAg) and anti-hepatitis C antibodies. The results show that HBsAg was not detected in the sera of all of the SLE patients. Only one patient was confirmed to have anti-HCV antibodies, suggesting that chronic infection with hepatitis B and C is not increased in patients with SLE compared with the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 6 publications
1
17
1
3
Order By: Relevance
“…These autoantibodies were chosen for the study because they are common antibodies in systemic autoimmune diseases such as systemic lupus erythematosus (SLE), Sjogren's syndrome (SS) and systemic sclerosis (SSc). Due to its lymphotropism, HCV has been reported to be associated with a broad spectrum of autoimmune manifestations, including cryoglobulinaemia, Sicca syndrome, vasculitis and lymphoproliferative disorders [2][3][4][5][6][7][8], but there remains some controversy as to whether it plays a role in the pathogenesis of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These autoantibodies were chosen for the study because they are common antibodies in systemic autoimmune diseases such as systemic lupus erythematosus (SLE), Sjogren's syndrome (SS) and systemic sclerosis (SSc). Due to its lymphotropism, HCV has been reported to be associated with a broad spectrum of autoimmune manifestations, including cryoglobulinaemia, Sicca syndrome, vasculitis and lymphoproliferative disorders [2][3][4][5][6][7][8], but there remains some controversy as to whether it plays a role in the pathogenesis of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The association of HCV infection and autoimmunity has been reported [2][3][4][5][6][7]. Several studies have suggested that chronic HCV may act as a trigger for the development of autoimmune rheumatic diseases [2][3][4][5][6][7][8]. The role of HCV in these disorders has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…In some epidemiological studies, the prevalence of HCV in patients with SLE was similar to those of anti-HCV antibodies found in the general population [8,52,53]. However, using polymerase chain reaction, other studies reported that the prevalence of HCV in patients with SLE was found to be higher than that in blood donors [8,51,54,55].…”
Section: Hcv Infection In Patients With Slementioning
confidence: 70%
“…Previous reports regarding the prevalence of HBV infection in lupus patients from various countries are summarized in Table 1 (Permin et al 1982;Bonafede et al 1986;Chng et al 1993;Abu-Shakra et al 1997;Lu et al 1997;Ram et al 2008;Watanabe et al 2013). In previous studies by other groups, anti-HBs and anti-HBc were measured with a radioimmunoassay that was less sensitive than CLIA used in our study ).…”
Section: Prevalence Of Hbv Infection In Lupus Patientsmentioning
confidence: 71%